2022
DOI: 10.1001/jamanetworkopen.2022.0527
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Associated With Influenza and Respiratory Syncytial Virus in the US, 1999-2018

Abstract: IMPORTANCERespiratory syncytial virus (RSV) mortality estimates have not been updated since 2009, and no study has assessed changes in influenza mortality after the 2009 pandemic. Updated burden estimates are needed to characterize long-term changes in the epidemiology of these viruses. OBJECTIVE To evaluate excess mortality from RSV and influenza in the US from 1999 to 2018. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study used data from 50.3 million US death certificates from 1999 to 2018 to crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
103
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 38 publications
4
103
1
4
Order By: Relevance
“…Several recent studies address these issues. Hansen et al undertook an evaluation of excess mortality using 1999–2018 US death certificate data similar to the classic analysis by Thompson et al [ 32 , 33 ]. They found that RSV accounted for an estimated 96 deaths in infants <12 months old each year, and infant mortality was 5-fold higher for RSV than for influenza over this period.…”
Section: Mortalitymentioning
confidence: 99%
“…Several recent studies address these issues. Hansen et al undertook an evaluation of excess mortality using 1999–2018 US death certificate data similar to the classic analysis by Thompson et al [ 32 , 33 ]. They found that RSV accounted for an estimated 96 deaths in infants <12 months old each year, and infant mortality was 5-fold higher for RSV than for influenza over this period.…”
Section: Mortalitymentioning
confidence: 99%
“…The relationship between patient age and mortality differs between seasonal and pandemic IAV infections. Unlike the seasonal IAV age risks noted above, pandemic IAV infections often disproportionately kill young adults, as has been well documented for the 1918 [ 1 , 5 ], 1968 [ 6 ], and even the 2009 [ 7 , 8 , 9 ] pandemics.…”
mentioning
confidence: 98%
“…As annual vaccination for influenza has been recommended for all US infants ≥6 months of age since 2003 [ 5 , 6 ], influenza mortality results are useful for comparison. In fact, a recent study reported that among US infants aged <1 year, excess mortality due to RSV was 5 times that of influenza from 1999 to 2018 [ 7 ]. While many influenza vaccines are available [ 8 ], palivizumab is the only immunoprophylaxis for RSV, recommended only for a subset of infants based on gestational age and comorbidity status [ 9 ].…”
mentioning
confidence: 99%
“…However, these studies only report disease burden and did not report mortality rates. Recently, Hansen et al [ 7 ] modeled excess RSV and influenza mortality rates for age groups including infants <1 year, using death certificate and surveillance data from 1999 to 2018. In another study, Hansen et al [ 20 ] reported death counts and population-based rates for age and race categories using NCHS death certificate data for 1999–2018, for purposes of comparing to prior excess mortality estimates of RSV, bronchiolitis, and influenza.…”
mentioning
confidence: 99%
See 1 more Smart Citation